Investigating The Internal And External Factors That Affect Growth Business Intention And Corporate Social Responsibility (CSR) Intention Among Small Medium Enterprise In Malaysia - Mohamad Karudin, Khairulazmi (2010)
This study is therefore designed based on Institutional Theory that consists regulatory, cognitive and nonnative as main dimensions to investigate the internal and external factors that will influence SME growth intention and SME CSR Intention in Malaysia. Penyelidikan ini telah dicetus berpandukan Teori Institusi yang terdiri daripada beberapa faktor iaitu dimensi regulatori, dimensi kognitif dan dimensi budaya persekitaran yang bertindak sebagai pembolehubah utama dalam kajian ini yang mempengaruhi niat untuk mengembangkan pemiagaan dan niat untuk mempraktiskan tanggungjawab sosia! dalam pemiagaan.